2007
DOI: 10.1590/s0103-84782007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Inibição do desenvolvimento de fungos fitopatogênicos por detergente derivado de óleo da mamona (Ricinus communis)

Abstract: No presente estudo avaliou-se o efeito fungitóxico do detergente derivado do óleo da mamona (Ricinus communis) sobre o desenvolvimento dos fitopatógenos: Pyricularia grisea, Fusarium graminearum e Colletotrichum lindemuthianum. Seis concentrações do detergente (12,5mL L-1 a 300mL L-1) foram, individualmente, incorporadas ao Meio Basal; a seguir, após inoculação fúngica, o crescimento radial dos micélios foi avaliado. A inibição total do desenvolvimento de C. lindemuthianum e P. grisea foi observada entre as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…It is noteworthy that no difference between treatments was found in the count of C. albicans and S. aureus , two important species found in the denture biofilm. Studies have reported that the detergent properties of R. communis cause damage to the cell wall, resulting in loss of the constituents of cytoplasm and subsequent cell death 12 , 30 . These action mechanisms however need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that no difference between treatments was found in the count of C. albicans and S. aureus , two important species found in the denture biofilm. Studies have reported that the detergent properties of R. communis cause damage to the cell wall, resulting in loss of the constituents of cytoplasm and subsequent cell death 12 , 30 . These action mechanisms however need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…é nativa da África tropical e atualmente, é cultivada em regiões tropicais e subtropicais do mundo (ALLAN et al, 2008). O óleo da mamona possui alto valor econômico em razão da sua versatilidade de aplicação na indústria, podendo ser utilizado na composição de cosméticos, de produtos farmacêuticos, de óleos lubrificantes, além de polímeros (ALLAN et al, 2008;SEVERINO et al, 2009;TAKANO et al, 2007). A versatilidade do óleo de mamona se deve à estrutura química do ácido ricinoléico (INTERNATIONAL CASTOR OIL ASSOCIATION -ICOA, 2008).…”
Section: Introductionunclassified
“…Castor oil, a natural derivative of the Ricinus communis plant, has a long history of therapeutic use. [54][55][56][57] It possesses recognised anti-inflammatory, 58 anti-nociceptive, 59 antioxidant, [60][61][62] anti-microbial, 63,64 insecticidal properties, 65 with a good safety and tolerance profile. 66,67 Recently, castor oil has found application within commercial ophthalmic eyedrop preparations, proving effective in counteracting tear film lipid insufficiency and tear film instability, and showing potential in managing dry eye disease secondary to meibomian gland dysfunction, without reported side effects.…”
Section: Treatmentmentioning
confidence: 99%